GROWTH RESPONSE OF GONGRONEMA LATIFOLIUM (AMARANTH GLOBE) TO SOURCES AND RATES OF ORGANIC MANURES IN AN ACID SOIL ENVIRONMENT OF TROPICAL REGIONS - EGBUCHUA, Collins; ENUJEKE, Emmanuel Chukudinife (International Journal of Research -GRANTHAALAYAH, 2021)
A field potted experiment was carried out in Asaba area of Delta State, Nigeria to evaluate sources and rates of organic manures (poultry and farmyard) on growth responses of Gongronema latifolium in an acid soil environment. It was a factorial experiment laid out in a randomized complete block design replicated 3 times. Data on plant height, number of leaves/branches, leaf area and stem girth were collected at 3, 5, 7, 9, 11 and 13 Weeks after sowing (WAS) and subjected to analysis of variance. The results that the effects on growth parameters of the crop were not significant and that higher application rates significantly increased plant height, number of leaves/branches and stem girth of G. latifolium. Application rates of 15 and 20 t/ha of both poultry and farm yard manures increased plant height from 10.45 cm to 12.52 cm and 8.12 cm and 10.68 cm respectively. The overall result indicated that the higher rate of organic manure, the better the response of growth indices of G. latifolium, though interaction effect was not significant. Poultry manure produced higher values of growth indices than farm yards manure, hence was recommended for increased productivity of G.latifolium in the study area.